THE INFLUENCE OF EXTERNAL PRESSURE, FINANCIAL STABILITY AND FINANCIAL TARGET ON FRAUDULENT FINANCIAL REPORTING (Empirical Study of Manufacturing Companies in the Consumer Goods Industry Sector Listed on the IDX 2016-2020) - Dinda Tri Novianty Divian; Arni Karina; Kumba Digdowiseiso (Jurnal Ekonomi, 2023)
This research aims to obtain empirical evidence on the influence of external pressure, financial stability and financial targets on fraudulent financial reporting in consumer goods industry manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. The population in this study are manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange via the websitewww.idx.co.idduring the 2016-2020 period. The samples in this research were 14 manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2016-2020 which were selected using a purposive sampling method. The type of data used in this research is secondary data. Data collection techniques and tools in this research use documentation and literature study methods. Meanwhile, the data analysis method used is multiple linear regression analysis. The results obtained in this research indicate that external pressure and financial targets have a significant negative effect on financial statement fraud. Meanwhile, financial stability does not have a significant effect on fraudulent financial statements.